The Biathlon Injury and Illness Surveillance (BIIS) project protocol: a prospective cohort study across two World Cup seasons. Issue 1 (27th November 2020) - Fitzpatrick, Jane; Panagodage Perera, Nirmala
Abstract : Introduction: Reliably and accurately establishing injury and illness epidemiology in biathletes will provide insight into seasonal changes, provide potential to better embed innovative prevention strategies and advance sports medicine through the provision of effective healthcare to biathletes. The main objective of the Biathlon Injury and Illness Study (BIIS) is to provide the first comprehensive epidemiological profile of injury and illness in biathlon athletes during two consecutive Biathlon World Cup seasons over 2-years. Methods: The BIIS study methodology is established in line with the International Olympic Committee (IOC) injury and illness surveillance protocols using a biathlon-specific injury and illness report form. Team medical staff will provide weekly data using injury and illness definitions of any injury or illness that receives medical attention regardless of time loss. Injuries or illness must be diagnosed and reported by a qualified medical professional (eg, team physician, physiotherapist) to ensure accurate and reliable diagnoses. Descriptive statistics will be used to identify the type, body region and nature of the injury or illness and athlete demographics such as age and gender. Summary measures of injury and illnesses per 1000 athlete-days will be calculated whereby the total number of athletes will be multiplied by the number of days in the season to calculate athlete-days. Ethics and Dissemination: This study has been approved by the Bellbery Human Research Ethics Committee (HREC reference: 2017-10-757). Results will be published irrespective of negative or positive outcomes and disseminated through different platforms to reach a wide range of stakeholders.